Implementation of SEEK in a Children's Advocacy Center: A Process Improvement Initiative. Issue 4 (23rd July 2022) - Letson, Megan M.; Brink, Farah W.; Daniels, Alicia; Thompson, Sandra; Wolf, Kathryn G.; Michaels, Nichole L.
Abstract : Introduction: Risk factors for child maltreatment are well-described, but clinicians may overlook these risk factors. The Safe Environment for Every Kid (SEEK) model is an evidence-based approach to identifying psychosocial risk factors for child maltreatment. This article describes a quality improvement initiative to implement the SEEK model in a unique pediatric setting, a Children's Advocacy Center. Methods: The objectives were to (1) describe the identification of psychosocial risk factors for child maltreatment by implementing the SEEK screening tool with each new family, (2) achieve and sustain a SEEK completion rate of greater than 85%, and (3) achieve and sustain a SEEK follow-up compliance rate of greater than 75%. Structured quality improvement methods, including several plan-do-study-act cycles, were used to implement interventions. Results: The percentage of caregivers who completed the SEEK questionnaire increased from a baseline of 76% to 86%, which was sustained for more than 2 years, resulting in a better understanding and support of families' needs. Caregivers completed 3, 606 SEEK Parent Questionnaire-R. Mental health concerns and food insecurity were among the most commonly endorsed items. Follow-up compliance increased from 47% to 90%, a level that has been maintained. Conclusions: While Children's Advocacy Centers evaluate children with suspected abuse, identifying current stressors in the home and linking families with resources to address their immediate psychosocial concerns can improve short- and long-term outcomes. This initiative demonstrates the feasibility of incorporating consistent screening for psychosocial risk factors for child maltreatment in this busy environment.